PENGGUNAAN BAHAN AJAR KITAB ḤADITṠ KULLA YAUM JILID I DALAM MENINGKATKAN KEMAMPUAN MUHADATSAH SISWA KELAS X IPS SMA TERPADU PONDOK PESANTREN NURUL HUDA - Nanda Nur Hanifa; Septi Wahyuni (Arabic Language and Education, 2024)
Abstrak:In an effort to improve the quality of teaching, the Nurul Huda Islamic Boarding School Integrated High School gives authority to teachers to find their own teaching references. One of the teachers, Mr. Anwar, chose the book